Structural and functional studies of peptide asparaginyl ligases - Hu, Side (Nanyang Technological University, 2022)
Asparaginyl endopeptidases are cysteine peptidases. Most AEPs are proteases, but some special AEPs known as peptide asparaginyl ligases (PALs), such as butelase 1, mediate peptide cyclization or ligation reactions. PALs and AEPs exhibit a high degree of amino acid sequence identity and structural similarity. So, what explains the difference in their activities? To investigate the ligation mechanism and the molecular and structural basis of ligase activity, we used a novel PAL, VyPAL2, from a cyclotide-producing plant, Viola yedoensis. Based on the proenzyme structure of VyPAL2, two sites, known as ligase activity determinants (LADs), were proposed to be involved in the ligase activity, as evidenced by mutagenesis on a protease-type AEP, butelase 2. To better understand the ligation mechanism, crystal structures of the active enzymes were obtained, including a catalytic Cys to Ala mutant (C214A). Activation of C214A showed that this mutant still retains the ability to auto-activate, while the ligase activity is largely lost. Further research suggests that the catalytic His could be the critical residue in the activation process. This suggests that different from previous understanding, the activation process and ligation process may be two separate processes sharing the same active sites, or the catalytic His might regulate the activity of the enzyme. Furthermore, one of the structures of the C214A active enzyme was found to be a complex structure, which was further confirmed to be a native substrate-enzyme complex. The structure confirms that the ‘gatekeeper’ residue of LAD1 affects the backbone positioning of the substrate and thus the ligase activity.